Delayed treatment seeking and its associated factors among people with schizophrenia spectrum disorders who are on follow-up at Dilla University Referral Hospital in the southern region of Ethiopia, 2022: a cross-sectional study - Negash, Misrak; Temesgen, Bethel; Kassaw, Chalachew; Abebe, Lulu; Moges, Solomon; Sime, Yohanes; Yimer, Solomon (Frontiers in Psychiatry, 2023)
Background Delay in psychiatric treatment leads to increased morbidity and mortality, as well as the emergence of several psychiatric and physical comorbidities and the use of life-threatening and life-altering self-treatments (such as licit and illicit substance misuse). Delaying detection and taking preventive measures against its modifiable factors are crucial for a better prognosis. Objective To assess delayed treatment seeking and its associated factors among people with schizophrenia spectrum disorders who are on follow-up at Dilla University Referral Hospital in the southern region of Ethiopia. Method An institution-based cross-sectional study was conducted between 8 June and 11 September at Dilla University Referral Hospital in the southern region of Ethiopia in 2022. Epicollect was used to collect data from 414 randomly selected participants using an interviewer-administered questionnaire. Delayed treatment seeking was determined using participants' medical records and a semi-structured questionnaire. The data were analyzed using Statistical Package for Social Sciences (SPSS) version 26. A logistic regression analysis was conducted to identify the explanatory variables for delayed treatment. Results The magnitude of delayed treatment seeking was 49.8% (95%CI = 44.9, 54.3). Study participants with disengaged family cohesion [AOR = 3.97, 95%CI = (2.999, 7.193)], inflexible family adaptability [AOR = 2.00, 95%CI = (1.686, 4.044)], who lack awareness about the availability of psychiatric treatment [AOR = 1.63, 95%CI = (1.362, 2.626)], high internalized stigma [AOR = 3.24, 95%CI = (2.770, 5.514)], and those with a negative attitude toward psychiatric treatment [AOR = 2.88, 95%CI = (2.034, 4.469)] had delayed seeking treatment. However, the participants whose educational status was higher than diploma [AOR = 0.040, 95%CI = (0.026, 0.077)] and high school [AOR = 0.09, 95%CI = (0.071, 0.204)] were less likely to have delayed seeking treatment. Conclusions There is a significant delay in seeking modern psychiatric treatment. Stigma, a lack of awareness of where treatment is available, disengaged family cohesion, inflexible family adaptability, distance to a health facility >5 km, and a negative attitude toward psychiatric treatment were barriers to seeking appropriate care.